Work Commitment as Mediation of the Relationship Between Competency and Work Motivation on Employee Performance in Asttatindo (Indonesian Expert and Skilled Engineering Association) - Chaidir, John; Zulfikar, Taufik (MIX: JURNAL ILMIAH MANAJEMEN, 2023)
Objective: The research objective was to analyze the influence of Employee competency s significantly on work commitment and employee performance the influence of work Competence on Work Commitment and Employee Performance, the influence of Work commitment on Employee Performance, and the role of work commitment as a variable mediating the relationship between competence and work motivation and employee performance.Methodology: This type of research uses survey research methods with a quantitative research approach. Survey research is intended to explain causal relationships and test hypotheses using the SEM-PLS model. SmartPls 4 v.4.0.9.4 is a multivariate statistical technique that compares exogenous with endogenous variables. The population of the study are members of Asttatindo, namely 24,000 construction workers who have had education and training and/or are members of Asttatindo. Sampling uses incidental sampling and purposive or judgment sampling, namely sampling based on the number of respondents who fill out the instrument and must match the proportion of the sample required in the SEM-SmartPls model. A minimum sample of 130 employee respondents is required. Incidental sampling can be achieved with 130 (between 130 -1000) respondents.Findings: Based on the results of hypothesis testing using Smart PLS it shows that: the first hypothesis (H1) is accepted because the t-count value is 8.483 < t table = 1.97 and the